Lung cancer patient with purulent complications – oncological or thoracic patient? (commentary to article Korymasov E.A. Et al. «Who, how and where should treat a patient with surgical complications of lung cancer (organizational, diagnostic, therapeutic, socio-ethical aspects)?») - A. A. Akopov; I. V. Deynega; A. S. Agishev (Вестник хирургии имени И.И. Грекова)
.